Cellular Imaging at 1.5 T: Detecting Cells in Neuroinflammation using Active Labeling with Superparamagnetic Iron Oxide - Ayman J. Oweida; Elizabeth A. Dunn; Paula J. Foster (Molecular Imaging)
The ability to visualize cell infiltration in experimental autoimmune encephalomyelitis (EAE), a well-known animal model for multiple sclerosis in humans, was investigated using a clinical 1.5-T magnetic resonance imaging (MRI) scanner, a custom-built, high-strength gradient coil insert, a 3-D fast imaging employing steady-state acquisition (FIESTA) imaging sequence and a superparamagnetic iron oxide (SPIO) contrast agent. An “active labeling” approach was used with SPIO administered intravenously during inflammation in EAE. Our results show that small, discrete regions of signal void corresponding to iron accumulation in EAE brain can be detected using FIESTA at 1.5 T. This work provides early evidence that cellular abnormalities that are the basis of diseases can be probed using cellular MRI and supports our earlier work which indicates that tracking of iron-labeled cells will be possible using clinical MR scanners.